(untitled) (Bodhi Path, 2025)
"Depictions of Buddha’s Life in Indian Art: Selected Sculptures from the National Museum, New Delhi" examines how important moments in the life of Siddhartha Gautama, also known as the Buddha, are shown artistically in Indian sculpture. These sculptures, which are kept in the National Museum in New Delhi, provide a visual tour of the pivotal moments in the life of the Buddha, from his conception to his realization of enlightenment. The spiritual core of Buddha’s life is preserved and communicated in large part through Indian art, especially sculpture. Important events including Siddhartha’s birth, his renunciation of the royal life, his enlightenment under the Bodhi tree, his first sermon, and his Mahāparinirvāṇa (death and ultimate release) are shown in the museum’s sculptures. The diverse range of creative techniques used to depict these stories reflects the cultural and religious diversity of India throughout its history. The sculptures’ theological and philosophical lessons are reflected in them in addition to their historical and aesthetic relevance. These artworks employ particular mudras, or hand movements, to represent many facets of Buddha’s teachings, including knowledge, compassion, and the ability to overcome suffering. These sculptures encourage people to consider the core ideas of Buddhism by acting as a visual and spiritual conduit. The National Museum provides a valuable perspective on how Indian art has preserved the life and legacy of Buddha over the ages through this collection. This article aims to study Buddha’s life episodes in different periods, regions, etc. through stone sculptures. It will be analyzed based on select sculptures.